The central repeat domain 1 of Kaposi's sarcoma-associated herpesvirus (KSHV) latency associated-nuclear antigen 1 (LANA1) prevents cis MHC class I peptide presentation - Kwun, Hyun Jin; da Silva, Suzane Ramos [UNESP]; Qin, Huilian; Ferris, Robert L.; Tan, Rusung; Chang, Yuan; Moore, Patrick S. (Academic Press Inc. Elsevier B.V., 2011)
KSHV LANA1, a latent protein expressed during chronic infection to maintain a viral genome, inhibits major histocompatibility complex class I (MHCI) peptide presentation in cis as a means of immune evasion. Through deletional cloning, we localized this function to the LANA1 central repeat 1 (CR1) subregion. Other CR subregions retard LANA1 translation and proteasomal processing but do not markedly inhibit LANA1 peptide processing by MHC I. Inhibition of proteasomal processing ablates LANA1 peptide presentation. Direct expression of LANA1 within the endoplasmic reticulum (ER) overcomes CR1 inhibition suggesting that CR1 acts prior to translocation of cytoplasmic peptides into the ER. By physically separating CR1 from other subdomains, we show that LANA1 evades MHC I peptide processing by a mechanism distinct from other herpesviruses including Epstein-Barr virus (EBV). Although LANA1 and EBV EBNA1 are functionally similar, they appear to use different mechanisms to evade host cytotoxic T lymphocyte surveillance. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Kaposi's sarcoma-associated herpesvirus; Latency-associated nuclear antigen 1; Major histocompatibility complex class I; Immune evasion